Financing SGD2 and ending hunger - Díaz-Bonilla, Eugenio (United Nations Food Systems Summit, 2021)
Among the important tasks of the UNFSS is identifying ways to finance the transformation of the global food system. This report analyses options for financing a specific, but crucial, part of the overall food system transformation, namely achieving SDG2 (and in particular “zero hunger”) by 2030 and examines the role of external finance in this effort. It reviews costs and possible resources and offers ideas for effective mobilization and use of the funds.